From memory to historical writing in the islamic heritage: “ The first three hijri centuries “ - azeez, hoshmand; Lashkry, Haidar (Humanities Journal of University of Zakho, 2023)
This research focuses on the importance of memory and the transition from remembering to writing in the Arab-Islamic heritage. We mean here The process of transformation from oral narration to writing and laying the scientific foundations for codification. This represents the issue of the transition from oral narration through remembrance, to the production of historical records in its founding era. Oral narration is one of the main sources of history writing. Where events are preserved and passed on, from one generation to another by remembrance. It becomes an important part of the historical discourse produced by civilization in its cultural dimension. Hence, memory represented one of the most important sources on which writing was nourished, especially historical, in the Islamic context. And it had a prominent and even sensitive role in preserving the past and fateful events in the first era of Arab-Islamic history and then re-embodied these events in the present lived the everyday life of Muslims, in which the process of remembering takes place, or is written down. From here, we try to shed light on how Arab-Islamic history was written, by referring to oral memory and the reliance of the first historians on oral narrations in their recording of events. Especially with regard to the interpretation of the Qur’an and the search for narrations related to the reasons for its revelation, or is the subject related to the hadiths of the Prophet, the Prophet’s biography, and the Maghazis. And then the events related to internal problems and conflicts until we reach the conquests and military expansion of the Muslim Arabs.